Human Settlements Interactions and Deforestation in Gambari Forest Reserve located in Oluyole Local Government Area (LGA) of Oyo State, Nigeria (2021)
This study was designed to examine changes in land cover types and the interaction of human settlements with the forest and impact of such interaction on the reserve. Community leaders and randomly selected community dwellers in each of the selected settlements were sampled for group discussion to obtain information on population and services of the forest that attract them to the reserve. Landsat images of 1984 and 2019 were used to extract land cover types using maximum likelihood classifier in Idrisi environment. The level of attractiveness and Interactions of the communities with the reserve were determined employing gravitational model. Results show that there was an increase in the size and number of settlements within the study area and decrease in in forest cover by 34% and 6.02% respectively. It was also revealed from the study that about 39% of the total area was taken over by development (building, roads and other classes) within the forest reserve, while 3% of the developed area gave way to forest cover. The degraded parts of the reserve in recent time was about 16% of the total reserve area and about 78% remained forest cover. From the results it is obvious that the level of interaction and imparts of such interaction depends on the community’s population size rather than distance. It is therefore imperative to regulate the activities of adjoining communities and those within the Gambari forest reserve by appropriate authorities.